Composición química de ensilaje de maíz y lodo de palma en diferentes proporciones - Villarroel Chávez, Myrka Dayanara (2022)
The research was carried out in the Experimental Campus "La María" of the State Technical University of Quevedo (UTEQ), the objective of the present investigation was to evaluate the chemical composition and palm mud in different proportions, for this investigation a completely at random (DCA), with